2017
DOI: 10.1016/j.jallcom.2017.07.262
|View full text |Cite
|
Sign up to set email alerts
|

Mn doped AIZS/ZnS nanocrystals: Synthesis and optical properties

Abstract: In this work, Mn doped AIZS/ZnS (Mn:AIZS/ZnS) nanocrystals (NCs) have been synthesized in an approach using heat-up and drop-wise addition of precursors. On the basis of the characterization of these doped NCs on their optical properties and materials, it is found that: (1) as more Mn atoms are doped into NCs, the doped NCs present photoluminescence (PL) red-shift and quantum yield quenching; (2) the doped NCs possess a short PL lifetime in tens of microseconds and a long PL lifetime in hundreds of microsecond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Note that the interaction would cause the further decrease of the lifetime (both the short lifetime and the long lifetime). The long lifetime is thought be due to the relatively isolated Mn dopants in the NCs [ 31 , 46 , 47 ]. The number of relatively isolated Mn dopants could be reduced with the incorporation of more Cu atoms into the host NCs, which would result in the decrease in the long lifetime.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the interaction would cause the further decrease of the lifetime (both the short lifetime and the long lifetime). The long lifetime is thought be due to the relatively isolated Mn dopants in the NCs [ 31 , 46 , 47 ]. The number of relatively isolated Mn dopants could be reduced with the incorporation of more Cu atoms into the host NCs, which would result in the decrease in the long lifetime.…”
Section: Resultsmentioning
confidence: 99%
“…As we know, the PL is one of the effective methods to detect the vacancy in photocatalysts. [46] As can be seen in Figure S2a, there are six emission peaks at 438, 450, 467, 482, 535 and 563 nm that can be observed, which can attribute to the emission of Zn-vacancy defect states of ZnSÀ V Zn . [47] A large number of zinc vacancies were discovered in the ZnS sample and accordant with the results of the XPS.…”
Section: Uv-vis Drs and Photoluminescence Analysismentioning
confidence: 87%
“…In this context, several reports showed that the amount of the metallic element used as dopant is critical, since it has a direct impact in both, structural and optical properties of the NPs. In this sense, Chen et al [30] showed that an increase of the levels of Mn acting as dopant gives rise to more defects in the nanostructure which leads to lower luminescent Quantum Yield (QY). Luminescence lifetimes , a parameter closely related to the electron-hole recombination processes and that therefore helps to understand the luminescence mechanism, were also affected by the level of Mn.…”
Section: Metal-doped Colloidal Inorganic Nanoparticlesmentioning
confidence: 99%